Endophytic and epiphytic microbes as “sources” of bioactive agents - Newman, David J.; Cragg, Gordon M. (Frontiers in Chemistry, 2015)
Beginning with the report by Stierle and Strobel in 1993 on taxol(R) production by an endophytic fungus 1, it is possible that a number of the agents now used as leads to treatments of diseases in man, are not produced by the plant or invertebrate host from which they were first isolated and identified.They are probably the product of a microbe in, on or around the macroorganism. At times there is an intricate “dance” between a precursor produced by a microbe, and interactions within the macroorganism, or in certain cases, a fungus, that ends up with the production of a novel agent that has potential as a treatment for a human disease. This report will give examples from insects, plants and marine invertebrates.